Physical illnesses associated with childhood homelessness - a literature review. (30th September 2020) - Strashun, S; D'Sa, S; Foley, D; Hannon, J; Murphy, A M; O'Gorman, C S
Abstract: Background and aims: Childhood homelessness is a growing concern in Ireland creating a Pediatric subpopulation at increased risk of physical illnesses, many with life-long consequences. Our aim was to identify and categorize the physical morbidities prevalent in homeless children. Methods: A review of the English-language literature on physical morbidities affecting homeless children (defined as < 18 years of age), published from 1999-2019 was conducted. A total of 1194 articles were identified, 33 articles of which met our inclusion criteria. Results: Respiratory issues were the most commonly cited illnesses affecting homeless children; including asthma, upper respiratory tract infections, and chronic cough. Homeless children were described as being at increased risk of contracting infectious diseases, many studies placing emphasis on STI and HIV/AIDS transmission. Dermatologic concerns comprised of scabies and head lice infestation, dermatitis, and abrasions. Malnutrition manifested as a range of physical morbidities; including childhood obesity, iron deficiency anemia, and stunted growth. Studies found a higher prevalence of poor dental and ocular health in this population as well. Many articles also commented on the risk factors predisposing homeless children to these physical health concerns, which can broadly be categorized as limited access to health care, poor living conditions, and lack of education. Conclusions: This literature review summarized the physical illnesses prevalent among homeless children and the contributing factors leading to them. Gaps in the literature were also identified, and included a dearth of studies focusing on younger children compared to adolescents. We believe that the current issue of child homelessness is socially and medically unacceptable and that homelessness occurring today will be one of the scandals of the next generation. Further research into prevention and intervention programs for this vulnerable population is urgently needed. Key messages: This literature review shows that homeless children are at an increased risk of several physical morbidities and identified the common themes among them. Based on this literature review, it is recommended that more research be done into developing appropriate intervention and prevention strategies to help this vulnerable population.